ANALISIS DAN PERANCANGAN SISTEM INFORMASI DATA INVENTARIS BARANG PADA SDN 111 KOTA JAMBI BERBASIS WEB - Khairunnisa, Fiqa; Ediansa, Oka; Yaakub, Saleh (LPPM Universitas Muhammadiyah Jambi, 2024)
An inventory information system has become an important requirement for various institutions, including schools. SD Negeri 111 Jambi City as one of the educational institutions in the region faces challenges in managing inventory of goods. Therefore, this research aims to analyze and design a web-based inventory information system that can help schools in managing their inventory. This research uses a system analysis and design approach to identify user needs and design an information system that suits these needs. Data collection methods used include observation, interviews and literature study. The results of observations and interviews conducted by researchers can serve as a guide in this research. The object development method used is UML (Unified Modeling Language), namely Use Case Diagrams, Activity Diagrams, and Class Diagrams. The system to be designed will allow users to record, monitor and track inventory of goods more easily and efficiently through a user-friendly web interface. Apart from that, this system can also increase the transparency and accuracy of inventory information and minimize the risk of data loss or omission. Thus, the development of a web-based inventory information system is expected to make a positive contribution in improving the performance at SD Negeri 111 Jambi City